2014
DOI: 10.1016/j.ijrobp.2014.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value and Reproducibility of Pretreatment CT Texture Features in Stage III Non-Small Cell Lung Cancer

Abstract: Purpose To determine whether pretreatment CT texture features can improve patient risk stratification beyond conventional prognostic factors (CPFs) in stage III non-small cell lung cancer (NSCLC). Methods and Materials We retrospectively reviewed 91 patients with stage III NSCLC treated with definitive chemoradiation. All patients underwent a pretreatment diagnostic contrast enhanced CT (CE-CT) followed by a 4D-CT for treatment simulation. We used the average (average-CT) and expiratory (T50-CT) images from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
172
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 174 publications
(178 citation statements)
references
References 25 publications
3
172
0
3
Order By: Relevance
“…In particular, the texture feature was the cluster shade of the Gaussian filtered image within the Laws feature group (Gauss cluster shade), To the best of our knowledge, we are the first researchers to report on the investigation of quantitative FDG PET image features (ie, radiomics) for predicting distant metastasis in early-stage NSCLC after SABR. Authors of other recent studies (24,25) have addressed early-stage NSCLC. Another strength of our study was that we focused on patients with early-stage NSCLC only and identified predictors that stratify patients of similar clinical stages, whereas authors of many previous studies included patients of mixed stages and did not address specifically whether the predictors add important information early-stage NSCLC by using a quantitative radiomic approach.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the texture feature was the cluster shade of the Gaussian filtered image within the Laws feature group (Gauss cluster shade), To the best of our knowledge, we are the first researchers to report on the investigation of quantitative FDG PET image features (ie, radiomics) for predicting distant metastasis in early-stage NSCLC after SABR. Authors of other recent studies (24,25) have addressed early-stage NSCLC. Another strength of our study was that we focused on patients with early-stage NSCLC only and identified predictors that stratify patients of similar clinical stages, whereas authors of many previous studies included patients of mixed stages and did not address specifically whether the predictors add important information early-stage NSCLC by using a quantitative radiomic approach.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, studies have suggested that the examination of spatial heterogeneity with computed tomography (CT) and the use of SUVs within solid tumors (particularly NSCLC) may provide prognostic information (8)(9)(10)(11)(12). Although these studies have generated compelling early evidence that heterogeneous tumors may lead to inferior outcomes, they have lacked adjustment for known prognostic factors and the use of proper validation techniques.…”
Section: Nuclear Medicine: Stage III Non-small Cell Lung Cancermentioning
confidence: 99%
“…In the context of tumor analysis, univariate or multivariate models using these features have typically been built to diagnose lesions, [13][14][15] identify secondary effects, 16 or predict outcome. 6,12 Recent publications have demonstrated that a wide variety of radiomics features may predict NSCLC patient outcomes when extracted from computed tomography (CT), 6,12,17 contrast-enhanced CT, 18,19 or positron emission tomography (PET) [20][21][22] images. However, no studies have yet examined whether there is a potential for imaging features extracted from cone-beam CT (CBCT) images to be useful.…”
Section: Introductionmentioning
confidence: 99%